Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ani12070838
|View full text |Cite
|
Sign up to set email alerts
|

One Health and Cattle Genetic Resources: Mining More than 500 Cattle Genomes to Identify Variants in Candidate Genes Potentially Affecting Coronavirus Infections

Abstract: Epidemiological and biological characteristics of coronaviruses and their ability to cross species barriers are a matter of increasing concerns for these zoonotic agents. To prevent their spread, One Health approaches should be designed to include the host (animal) genome variability as a potential risk factor that might confer genetic resistance or susceptibility to coronavirus infections. At present, there is no example that considers cattle genetic resources for this purpose. In this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(100 reference statements)
1
0
0
Order By: Relevance
“…However, the amino acid sequence of ACE2 is highly conserved in cattle (83% homology) [ 35 ] and cattle share four of the five hotspot residues with humans, suggesting a good probability of interaction between ACE2 and the spike protein of SARS-CoV-2 [ 36 ]. Other studies confirmed these data [ 37 , 38 , 39 ]. In humans, ACE2 is mainly expressed by the epithelial cells of the lung, intestine, kidney, heart, and blood vessels [ 36 ].…”
Section: Discussionsupporting
confidence: 70%
“…However, the amino acid sequence of ACE2 is highly conserved in cattle (83% homology) [ 35 ] and cattle share four of the five hotspot residues with humans, suggesting a good probability of interaction between ACE2 and the spike protein of SARS-CoV-2 [ 36 ]. Other studies confirmed these data [ 37 , 38 , 39 ]. In humans, ACE2 is mainly expressed by the epithelial cells of the lung, intestine, kidney, heart, and blood vessels [ 36 ].…”
Section: Discussionsupporting
confidence: 70%